Assessing Student Stress in Clinical Laboratory Science Programs: Online Versus Face-to-Face...American Society for Clinical Laboratory Science (ASCLS) Clinical Laboratory Educators’ Conference (CLEC), February 25-27, 2016 in Minneapolis, Minnesota. - Hendrix, Ericka (Clinical Laboratory Science)
Student stress is an issue that all clinical laboratory programs must address. The amount of stress that students perceive can impact grades, physical and mental health, and learning ability. Additionally, many programs have moved to online formats in which student stress is more difficult to detect. This study surveyed face-to-face clinical laboratory science students and online clinical laboratory students for perceived stress and coping mechanisms to determine differences in perceived stress and coping mechanisms. This study used a causal-comparative cross sectional design using inferential statistics to determine differences in perceived stress. Non-parametric tests were used to determine the differences in frequencies of coping mechanisms. Finally, correlational studies were conducted to determine if there was a relationship between student achievement (GPA) and perceived stress scores. The results of this study indicated that there was not a significant difference between online and traditional student perceived stress. Secondly, the results indicated that there was not a significant difference between face-to-face and online students use of coping mechanisms. Finally, the results of the study showed there was a significant correlation between perceived stress and GPA for student enrolled in the face-to-face program, but this was not the result for the online students. These results are useful for administrators and faculty to develop curricula that addresses stress, coping, and academic success for both online and face-to-face clinical laboratory science programs.